Pendidikan Karakter Sufistik dalam Cerita Anak Bergambar Awas Manusia Karya Ahmad Mustofa Bisri Berbasis Elektronik - Anwar, Fikrul; Busri, Hasan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The research aims to describe the characteristics of Sufis. This type of research uses descriptive qualitative. The descriptive qualitative type is to explain how to describe the phenomena that have been found. The data obtained were obtained from an electronic picture story book entitled Beware of Humans by Ahmad Mustofa Bisri. The method used in collecting data is through reading, note-taking and documentation stages. This research is important to carry out to describe the results of the data found, because there are two components of the data contained in the book, namely, the characteristics of a Sufi, namely caring, friendly and humble, both of which are the basis of human nature when interacting with society and its environment. so that humans will have the important nature of peace and avoid disputes. Interestingly, the caring, friendly and humble character described by the author is an animal. The electronic reading book for children with the title Beware of Humans tells the story of the world of animals which can easily educate children in character development.